Identification of drought responsive Elaeis guineensis WRKY transcription factors with sensitivity to other abiotic stresses and hormone treatments - Lee, Fong Chin; Yeap, Wan Chin; Appleton, David Ross; Ho, Chai Ling; Kulaveerasingam, Harikrishna (BioMed Central, 2022)
Background: The ability of plants to withstand and thrive in an adverse environment is crucial to ensure their survivability and yield performance. The WRKY transcription factors (TFs) have crucial roles in plant growth, development and stress response, particularly drought stress. In oil palm, drought is recognized as one of the major yield limiting factors. However, the roles of WRKY TFs in the drought response of oil palm is unclear. Results: Herein, we studied the transcriptome of drought treated oil palm leaf and identified 40 differentially expressed genes (DEGs) of WRKY TFs, of which 32 DEGs were upregulated and 8 DEGs were downregulated in response to drought stress in oil palm. They were categorized into Groups I to IV based on the numbers of WRKY domain and the structural difference in the zinc finger domain. Multiple stress- and hormone-responsive cis-regulatory elements were detected in the drought responsive oil palm EgWRKY (Dro-EgWRKY) genes. Fourteen of the 15 selected oil palm WRKY (EgWRKY) genes demonstrated a tissue-specific expression profile except for EgWRKY28 (Group I), which was expressed in all tissues tested. The expression levels of 15 candidate EgWRKYs were upregulated upon salinity and heat treatments, while several genes were also inducible by abscisic acid, methyl jasmonate, salicylic acid and hydrogen peroxide treatments. Members of the Group III WRKY TFs including EgWRKY07, 26, 40, 52, 59, 73 and 81 displayed multiple roles in drought- and salinity-response under the modulation of phytohormones. Conclusions: EgWRKY TFs of oil palm are involved in phytohormones and abiotic stress responses including drought, salinity and heat. EgWRKY07, 26, 59 and 81 from Group III maybe important regulators in modulating responses of different abiotic stresses. Further functional analysis is required to understand the underlying mechanism of WRKY TFs in the regulatory network of drought stress.